How to Prevent Burnout and Improve Performance?: The Role of Perceived Autonomy and Spirituality to Achieve Higher Performance - Ariani, Dorothea Wahyu (The journal of religion & society, 2020)
The purpose of this study was to examine the relationship model of perceived autonomy, spirituality, burnout, and performance. The research was conducted on undergraduate students in Indonesian universities, especially Yogyakarta University as a community that upholds collectivistic values. This study uses 628 responses. Validity and reliability testing were used to test the accuracy of the survey instruments. Correlation testing was conducted to explore the relationship between variables used in this study. Regression analysis was used to test the effect of perceived autonomy, spirituality, and burnout on performance. The results show that perceived autonomy actually reduced burnout. Burnout can reduce performance, but spirituality can improve performance. Mediating model testing was done using Structural Equation Modeling. Burnout was found to partially mediate the link between spirituality and performance and to fully mediate the relationship between perceived autonomy and performance. Although spirituality was related to burnout, the results of mediating model testing indicated that spirituality has no effect on burnout. This article presents an in-depth discussion of the results of the research analysis.